A influência da abordagem de ensinar do professor no uso da apostila Open Doors em um curso livre de inglês da prefeitura de Guarulhos: uma análise à luz da Operação Global de Ensino de Línguas - Martins, Daniel Fagundes (Universidade Federal de São Carlos, 2025)
This doctoral thesis aims to investigate, in light of the Global Operation of Language Teaching (OGEL), how the Teacher’s Teaching Approach influences the use of the Open Doors textbook in a municipal public English course offered by the city of Guarulhos. The language project, targeted at residents aged 13 and older, uses didactic materials developed by the teachers themselves. The study is grounded in the theoretical principles of the OGEL framework, with a specific focus on the Teacher’s Teaching Approach (Almeida Filho, 1997; 2002[1993], 2023) and the constructs of activity, exercise, pre-communicative task, and communicative task, as defined by Barbirato (1999; 2005). This is a qualitative study with ethnographic and documentary orientation, involving three tenured teachers from the municipal school system, all of whom hold degrees in Language Studies with certification in English. Data were collected through questionnaires, interviews, classroom observations and recordings, and analysis of the materials used. The relevance of this study lies in analyzing how teachers exercise autonomy in adapting and resignifying the Open Doors textbook to respond to the educational demands of the local public context. By investigating this dynamic, the research highlights teaching practices that go beyond the prescribed use of the material, revealing processes of resignification, tensions, and coherence between the teaching approach and the didactic material. The findings provide insights into how the field of ideas (teaching approach) influences the field of materialities (classroom procedures), as theorized in the OGEL model. The study thus contributes to the development of more contextualized and communicative pedagogical practices in language teaching, reinforcing the importance of teacher autonomy in public education.
The influence of the teacher’s teaching approach on the use of the Open Doors booklet in a non-formal English education program in Guarulhos, Brazil: an analysis through the lens of the Global Operation of Language Teaching
Keywords: Operação global de ensino de línguas; Abordagem de ensinar do professor; Material didático; Tarefas comunicativas; Comunicativização; Global operation of language teaching; Teacher’s teaching approach; Teaching material; Communicative tasks; Communicativization; LINGUISTICA, LETRAS E ARTES::LETRAS::LINGUAS ESTRANGEIRAS MODERNAS